Establishing a Core Outcome Measure for Life Participation: A Standardized Outcomes in Nephrology-kidney Transplantation Consensus Workshop Report. Issue 6 (June 2019) - Ju, Angela; Josephson, Michelle A.; Butt, Zeeshan; Jowsey-Gregoire, Sheila; Tan, Jane; Taylor, Quinetta; Fowler, Kevin; Dobbels, Fabienne; Caskey, Fergus; Jha, Vivekanand; Locke, Jayme; Knoll, Greg; et al.
Abstract : Background: Kidney transplantation confers substantial survival and quality of life benefits for many patients with end-stage kidney disease compared with dialysis, but complications and side effects of immunosuppression can impair participation in daily life activities. Life participation is a critically important patient-reported outcome for kidney transplant recipients but is infrequently and inconsistently measured in trials. We convened a consensus workshop on establishing an outcome measure for life participation for use in all trials in kidney transplantation. Methods: Twenty-five (43%) kidney transplant recipients/caregivers and 33 (57%) health professionals from 8 countries participated in 6 facilitated breakout group discussions. Transcripts were analyzed thematically. Results: Four themes were identified. Returning to normality conveyed the patients' goals to fulfill their roles (ie, in their family, work, and community) and reestablish a normal lifestyle after transplant. Recognizing the diverse meaning and activities of "life" explicitly acknowledged life participation as a subjective concept that could refer to different activities (eg, employment, recreation, family duties) for each individual patient. Capturing vulnerability and fluctuations posttransplant (eg, due to complications and side-effects) distinguished between experiences in the first year posttransplant and the long-term impact of transplantation. Having a scientifically rigorous, feasible, and meaningful measure was expected to enable consistent and frequent assessment of life participation in trials in kidney transplantation. Conclusions: A feasible and validated core outcome measure for life participation is needed so that this critically important patient-reported outcome can be consistently and meaningfully assessed in trials in kidney transplantation to inform decision making and care of recipients. Abstract : Supplemental Digital Content is available in the text.